Chemical Quality of Male Etawah Crossbred and Castrated Boer Crossbred Goat Meat - Djalal Rosyidi; Lilik Eka Radiati; Nadhirotul Uyun (Jurnal Ilmu dan Teknologi Hasil Ternak (JITEK), 2009)
The aim of this study was to know the chemical quality (moisture, protein, fat, calcium, phosphorus) of male Etawah crossbred and castrated Boer crossbred goat meat. The result expected can be used as further information about the chemical quality of male Etawah crossbred and castrated Boer crossbred goat meat and as future researches. The material of the research were loin meat, front and back thigh of male Etawah crossbred and castrated Boer crossbred goat, these meat parts were the fineground and 10 gram were taken for sample preparation. The result show that the different species of goat statistically was no significant effect (P>0.05) on moisture, protein, fat, calcium andÂ  phosphorus. The chemical quality of male Etawah crossbred and castrated Boer crossbred goat (moisture obtained from vacuum oven, fat from soxhlet, protein from semimicro kejldahl, calcium and phosphorus from Spectrophotometer) is (71.080%, 69.886%; 17.120%, 17.907%; 8.358%, 8.981%; 13.846 mg/100g, 18.811mg/100g; 134.817mg/100g, 151.032mg/100g). The conclusion was moisture content from male Etawah crossbred was higher than castrated Boer crossbred, but fat, protein, calcium, and phosphorus content castrated Boer crossbred were higher than castrated Boer crossbred. Â  Keywords: male Etawah crossbred, castrated Boer crossbred, moisture